2017
DOI: 10.1097/mat.0000000000000575
|View full text |Cite
|
Sign up to set email alerts
|

An International Survey on Ventilator Practices Among Extracorporeal Membrane Oxygenation Centers

Abstract: Although the optimal ventilation strategy is unknown for patients placed on extracorporeal support, there are increasing reports of extubation being used. Our objective was to describe the change in ventilation strategies and use of tracheostomy and bronchoscopy practices among extracorporeal membrane oxygenation (ECMO) centers across the world. A descriptive, cross-sectional 22 item survey of neonatal, pediatric, and adult ECMO centers was used to evaluate ventilator strategies, extubation, bronchoscopy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…The need for re-recruitment may prolong the ECMO course and contribute to VILI. Given this concern, some intensivists no longer practice strict "lung rest" while on ECMO for ARDS [90]. The most popular new ventilation practice is an open-lung strategy on ECMO, similar to the adult ARDS low V T ventilation strategy [91].…”
Section: Ventilator Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The need for re-recruitment may prolong the ECMO course and contribute to VILI. Given this concern, some intensivists no longer practice strict "lung rest" while on ECMO for ARDS [90]. The most popular new ventilation practice is an open-lung strategy on ECMO, similar to the adult ARDS low V T ventilation strategy [91].…”
Section: Ventilator Managementmentioning
confidence: 99%
“…Though there are only a few reports of bronchoscopy on ECMO in the literature [98][99][100][101], it is commonly implemented in clinical practice. Routine bronchoscopy of patients on ECMO is performed in 55% of pediatric ECMO centers and 76% of adult centers [90]. While the benefits of bronchoscopy on ECMO have not been established in the literature, they are often seen at the bedside in patients with thick respiratory secretions that cannot be mobilized through traditional suctioning techniques.…”
Section: Secretion Clearance On Ecmomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study looking at pediatric respiratory failure and ECMO support found a diagnosis of asthma to be independently associated with lower mortality with the lowest mortality of any diagnostic group . Extubation while on ECMO support is being increasingly utilized with more than 50% adult centers and more than 25% pediatric centers reporting it . We describe our recent experience of three patients in the winter of 2018‐2019 with NFA requiring ECMO support and review the current literature on this subject.…”
Section: Introductionmentioning
confidence: 97%
“…3 Extubation while on ECMO support is being increasingly utilized with more than 50% adult centers and more than 25% pediatric centers reporting it. 5 We describe our recent experience of three patients in the winter of 2018-2019 with NFA requiring ECMO support and review the current literature on this subject. The requirement for patient consent to publish this case report was waived by our Institutional Review Board in accordance with their policy.…”
Section: Introductionmentioning
confidence: 99%